2022
DOI: 10.1002/adfm.202203964
|View full text |Cite
|
Sign up to set email alerts
|

NIR‐II Photo‐Amplified Sonodynamic Therapy Using Sodium Molybdenum Bronze Nanoplatform against Subcutaneous Staphylococcus Aureus Infection

Abstract: Ultrasound (US)‐mediated sonodynamic therapy (SDT) has the advantages of non‐invasiveness and deep tissue penetration. Nanosystems are prominently used in sonosensitization; however, most nano‐sonosensitizers have a low reactive oxygen species (ROS) yield, thus restraining the application of SDT. Sodium molybdenum bronze nanoparticles (SMB NPs) with rich oxygen vacancies are developed and interlayer gaps of molybdenum trioxide nanobelts are expanded. Owing to the increased oxygen vacancy density and wide inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(48 citation statements)
references
References 42 publications
0
42
0
Order By: Relevance
“…Besides the aforementioned well-known methods, some other methods have also been reported for the preparation of Mo-NMs toward PTT application. [76,107,[189][190][191] For example, Yin et al reported a two-step method to achieve high-yield exfoliation of MoS 2 nanosheets from their bulk crystals. [189] The MoS 2 bulk crystals were first ground into thin flakes by NaCl-assisted ball-milling process and the resultant MoS 2 flakes were further treated with oleum at 90 °C for 8 h followed by sonication treatment to obtain ultrathin MoS 2 nanosheets.…”
Section: Other Methodsmentioning
confidence: 99%
“…Besides the aforementioned well-known methods, some other methods have also been reported for the preparation of Mo-NMs toward PTT application. [76,107,[189][190][191] For example, Yin et al reported a two-step method to achieve high-yield exfoliation of MoS 2 nanosheets from their bulk crystals. [189] The MoS 2 bulk crystals were first ground into thin flakes by NaCl-assisted ball-milling process and the resultant MoS 2 flakes were further treated with oleum at 90 °C for 8 h followed by sonication treatment to obtain ultrathin MoS 2 nanosheets.…”
Section: Other Methodsmentioning
confidence: 99%
“…Finally, 10 ul CCK8 was added and incubated for 0.5–4 h, absorbance at 450 nm was determined. ( Guo et al, 2021 ; He et al, 2022a ; Hu et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, molybdenum-based nanoparticles are promising probe for various biomedical applications such as drug delivery, diagnostics, bio-imaging. Mo NPs can generate ROS under ultrasound, and it enables noninvasive treatment using Mo NPs with high penetration depth exceeding 10 cm [177,178]. Although molybdenum has relatively high biocompatibility, it is still necessary to investigate the biocompatibility characteristics according to their size, shape, and crystallinity.…”
Section: Biosafety Of Molybdenum-based Nanotheranosticsmentioning
confidence: 99%